Determinants of community-acquired pneumonia among under-five children in Awi Zone, Northwest Ethiopia - Birhan, Nigussie Adam; Workineh, Alene Yirsaw; Wolde, Zelalem Meraf; Abich, Emebiet; Alemayehu, Gedif Mulat; Nigussie, Atalaye; Alemu, Yenew; Messfin, Chalachew Alemie; Belay, Denekew Bitew (Frontiers in Public Health, 2025)
BackgroundGlobally, community-acquired pneumonia is the leading cause of death in under-five children, accounting for 7.6 million deaths. Among these deaths, approximately 99% occur in low and middle-income countries. The present study aimed to assess the magnitude of community-acquired pneumonia and its associated factors among under-five children in Awi Zone.MethodsA community cross-sectional study was conducted on 1,368 participants from March to July 2023. A multistage sampling method was used. Data were entered into Epi-Data and exported to STATA for analysis. Bivariable and multivariable logistic regressions were used. Variables with a p-value of < 0.05 were considered statistically significant.ResultsThe percentage of community-acquired pneumonia among under-five children was 11.33% (95% CI: 9.75–13.12%). Primary education [AOR = 0.38; 95% CI:0.15, 0.95], stunting [AOR = 4.80; 95% CI: 2.31, 9.94], diarrhea [AOR = 3.75; 95% CI: 1.96, 7.18], acute lower respiratory tract infection [AOR = 14.57, 95% CI: 3.18, 66.78], acute upper respiratory tract infection [AOR = 9.06; 95% CI: 2.03, 40.42], and presence of separate kitchen [AOR = 0.38, 95% CI: 0.20, 0.72] were associated with community-acquired pneumonia.ConclusionIn this study, the percentage of community-acquired pneumonia was relatively high. Hence, we recommend adequate health education in areas such as nutritional intervention, the prevention and early treatment of diarrhea and acute respiratory tract infections (ARTI), and preventing indoor air pollution to reduce the risk of community-acquired pneumonia.